Operational Research Methods in Business, Finance and Economics Proceedings of the 31st European Conference on Operational Research, Athens, Greece, July 11-14, 2021 - Zopounidis, Constantin; Liadaki, Angeliki; Eskantar, Marianna (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book gathers selected high-quality papers presented at the 31st European Conference on Operational Research, which was held in Athens, Greece on June 11-14, 2021. It highlights the latest advances in the application of operations research (OR) to technology-driven areas in business, finance, and economics, covering both theoretical and methodological developments, as well as real-world case studies. It also explores the connections between OR and other analytical disciplines, such as soft computing and computer science, which can promote the development of new decision support technologies. .
Keywords: Operations research; Management science; Mathematical optimization; Operations Research and Decision Theory; Operations Research, Management Science .; Optimization